Institutional and emotion work in forensic psychiatry: detachment and desensitisation - Hui, Ada M.L. (Palgrave Macmillan, 2017)
Mental health professionals are frequently tasked with balancing care, safety and security. They are obliged to meet professional, organisational and institutional standards. Yet, these roles, expectations and practices are often in contention, whilst personal feelings and values are often ignored. This raises questions as to what the processes are in attempting to reconcile personal, professional and organisation conflict, how workers manage their emotions, and ultimately, what impacts these have upon those conducting such work, as well as those receiving care.